Role of lipoprotein (a) in peripheral arterial disease - Kosmas, Constantine E.; Silverio, Delia; Sourlas, Andreas; Peralta, Richard; Montan, Peter D.; Guzman, Eliscer; Garcia, Mario J. (Annals of Translational Medicine, 2019)
Lipoprotein (a) [Lp(a)] is a complex polymorphic lipoprotein synthesized by the liver, which is structurally similar to low-density lipoprotein (LDL). Like the LDL molecule, Lp(a) is composed of apolipoprotein B-100 (ApoB-100) but differs in that its ApoB-100 molecule is attached to apolipoprotein (a) [apo(a)], a polymorphic glycoprotein not found in the LDL molecule (1). Plasma levels of Lp(a) are primarily genetically determined by the LPA gene locus, independently of dietary or environmental factors (2).